A interação na família com adolescentes usuários da internet - Albuquerque, Olga Matilde Borges Correia de (2002)
The Internet is an actual phenomenon and begins to constitute an object of investigation by researchers from different areas of knowledge. It is a very complex phenomenon, triggering deep changes in human society and its constituent groups, among which the familiar group. At first, its use and procedures were very complicated, but has become easier and more accessible, what has converted it, during the last decade, in one popular phenomenon around the world. As it has gained domestic space, the adolescents, considered the "net geration", seem to be the greatest users of this new communication media. The present study, a qualitative assessment, aimed to analyse the interaction with internet-user adolescents withing the family, based on interviews with their parents. The research involved four couples, parents of male 13 to 16 year-old adolescents, totalling eight participants. Results give evidence that, under the respondent perspective, the internet constitutes a source of considerable conquests for contemporary youths, though it also causes losses that cannot be ignored nor neglected. Furthermore, the study evidencesthat the introduction of personal computer with internet conetion in their homes has triggered some sort of change on familiar interaction. We sougt to analyse this interaction under the framework of conquests and losses pointed out by the parents. This analysis also contributed for strengthening the idea of internet as a tool that integrates the range of many forces responsible by the production of family ubjectivity. Obtained results open new pers´ctives of investigation that can contribute to the work whith family